1993
DOI: 10.1111/j.1399-3038.1993.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Why do asthmatic children need referral to an emergency room?

Abstract: Asthmatic attacks continue to be a major cause of referral to the emergency room (ER), despite currently available effective treatments. We have prospectively evaluated 100 consecutive children who were referred to the ER with acute asthma and were followed by their primary physicians. Only 46% were able to recognize acute attacks, and 26% had the knowledge and skills for self-management. The prophylactic therapy recommended was usually appropriate, but the compliance was poor and mean serum theophylline level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although the ED is an appropriate setting for asthma care in emergent situations, some studies suggest that some ED asthma visits can potentially be avoided with appropriate outpatient care (3)(4)(5). It is estimated that the cost of an ED asthma visit is five times greater than the cost of an outpatient asthma visit (6).…”
Section: Introductionmentioning
confidence: 99%
“…Although the ED is an appropriate setting for asthma care in emergent situations, some studies suggest that some ED asthma visits can potentially be avoided with appropriate outpatient care (3)(4)(5). It is estimated that the cost of an ED asthma visit is five times greater than the cost of an outpatient asthma visit (6).…”
Section: Introductionmentioning
confidence: 99%
“…37 In a study comparing groups of children who had asthma seen in the ED to those seen in asthma clinic, selfreported non-adherence was higher in those seen in the ED. 38 Similarly, caregiver report of more non-adherence was associated with more ED visits for children who had asthma. 39 In contrast, a third study using a self-report measure of adherence found no relationship between non-adherence and ED visits when included in a multivariate model.…”
Section: Medication Non-adherence and Ed Visitsmentioning
confidence: 99%
“…We now have available several effective drugs for the pharmacological treatment of asthma, but patients’ information and education remain a cornerstone of long‐term management, as international guidelines underline (1–6). Educational programs for children with asthma and their families are intended to improve the knowledge of asthma, assess the severity of symptoms, know which medications to use, and decide when to seek medical care.…”
mentioning
confidence: 99%